URGENSI PELINDUNGAN HAK PRIORITAS (PRIORITEITRECHTS) ATAS ASET TANAH BUMN YANG DIPEROLEH DARI UNDANG-UNDANG NASIONALISASI YANG DIKUASAI OLEH PIHAK KETIGA SECARA MELAWAN HUKUM - Sumarno, Cecep; Pandamdari, Endang (Jurnal De Lege Ferenda Trisakti, 2024)
The complex land law issues upstream are affecting the stagnation of land law enforcement. Law enforcement by administrators is not adequately carried out, as the trend is always directed towards court resolutions (District Court Decision Selong No. 64/Pdt.G/2019/PN. Sel). Similarly, the enforcement of rights or certification often perceived as illegal is frequently seen as a discretionary matter, rather than a criminal one. The enforcement of land use and land utilization seems to be separated from land law enforcement, which should be carried out by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (Ministry of ATR/BPN). The author believes that there should be a collaborative effort among the Ministry of ATR/BPN, including the Regional Office of ATR/BPN in the Province and the Land Offices at the District/City level, the Corruption Eradication Commission (KPK), the Provincial Government down to the District/City Governments, State-Owned Enterprises Branch Offices in the Province and District/City, as well as the High Prosecutor's Office and the District Prosecutor's Office to carry out land and building registration activities in their respective areas, in accordance with land law regulations and land registration, while also considering the relevant laws and their implementing regulations